Development of a novel agar-based microtitre plate system for construction of consistent biofilm models and subsequent use in antimicrobial screening - Davies, Michaela Roxanne (Rhodes University, Faculty of Science, Biotechnology Innovation Centre)
Restricted access. Expected release in 2026.
Keywords: Uncatalogued